The ectomycorrhizal fungus Scleroderma bovista improves growth of hazelnut seedlings and plays a role in auxin signaling and transport - Cheng, Yunqing; Sun, Siyu; Lou, Hanxiao; Dong, Yutong; He, Hongli; Mei, Qi; Liu, Jianfeng (Frontiers in Microbiology, 2024)
Scleroderma bovista can form symbiotic ectomycorrhiza with hazel roots, facilitating the growth and development of host plants and fungi. This study aimed to evaluate the effect of ectomycorrhizal fungus S. bovista on the growth and development of hazel roots and gene expression changes through comparative transcriptome analysis. After inoculation with S. bovista, the fungus symbiotically formed ectomycorrhiza with hazel roots. The fresh weights of the aboveground and underground parts of My treatment (inoculated with S. bovista and formed mycorrhiza) were much higher than those of the control, respectively. The length, project area, surface area, volume, forks, and diameter of the inoculated seedlings root were 1.13 to 2.48 times higher than those of the control. In the paired comparison, 3,265 upregulated and 1,916 downregulated genes were identified. The most significantly enriched Gene Ontology term for the upregulated Differentially Expressed Genes was GO:0005215 (transporter activity). Immunohistochemical analysis suggested that the expression levels of auxin and Auxin Response Factor9 were significantly increased by S. bovista after the formation of mycorrhizal fungi in hazelnut root tips. These results indicate that genes related to auxin biosynthesis, transport and signaling, and transport of nutrients may contribute to root development regulation in hazel ectomycorrhiza.